2023
DOI: 10.5152/eurasianjmed.2022.22300
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in Behcet’s Disease, a Brief Review of the Literature

Abstract: Behcet’s disease is a chronic vasculitis of unknown etiopathogenesis. Serum vitamin D levels have been reported to be associated with a variety of inflammatory and autoimmune diseases one of which is Behcet’s disease. The previous studies about vitamin D in Behcet’s disease seem to be focused on 4 main categories; the studies evaluating serum vitamin D levels between patients with Behcet’s disease and controls, the studies evaluating serum vitamin D in the susceptibility and pathogenesis of Behcet’s disease, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Melikoğlu et al showed that oral ulcers and arthralgia were more common in patients below 30 years of age, while no significant difference was observed between age groups regarding disease activity. 22 In the present study, the mean age of patients with BD at onset was 27.98 ± 10.47 years. Studies in different countries have reported ages ranging between 26 and 35.7 years.…”
Section: Discussionmentioning
confidence: 47%
“…Melikoğlu et al showed that oral ulcers and arthralgia were more common in patients below 30 years of age, while no significant difference was observed between age groups regarding disease activity. 22 In the present study, the mean age of patients with BD at onset was 27.98 ± 10.47 years. Studies in different countries have reported ages ranging between 26 and 35.7 years.…”
Section: Discussionmentioning
confidence: 47%